Pan-cancer analysis identifies proteasome 26S subunit, ATPase (PSMC) family genes, and related signatures associated with prognosis, immune profile, and therapeutic response in lung adenocarcinoma - Jia, Hui; Tang, Wen-Jin; Sun, Lei; Wan, Chong; Zhou, Yun; Shen, Wei-Zhong (Frontiers in Genetics, 2023)
Background: Proteasome 26S subunit ATPase (PSMC) family members serve a critical role in regulating protein degradation and are essential for the tumor growth, however, little is known about the integrative function and prognostic significance of them in the lung cancer. Methods: We utilized consensus clustering and LASSO Cox regression, COX-BOOST and Survival random forest analysis in TCGA and GSE72094, a PSMC-based prognostic signature was created. We validated it in three independent cohorts from GEO and estimated its associated clinical, genomic and immune profiles, and the sensitivity to chemotherapy and immunotherapy. Twenty-one LUAD patients were enrolled in our local cohort and submitted tumor samples for evaluating the risk gene and PD-L1 expression. Results: The PSMC-based prognostic signature dichotomized LUAD patients according to the median risk score, and the predictive accuracy for predicting survival at 1- to 5-year in the training cohorts all exceeded 0.71. Furthermore, risk score exhibited positive correlation with TIDE and CD276 and CD274 expression, but lower immune score accompanied with decreasing abundance of B and CD8+ T cells. Finally, high risk patients were estimated to be less sensitive to immunotherapy but have higher possibility to respond to platinum-based chemotherapy. LUAD samples from our local cohort supported the findings in the expression difference of these five hub genes between tumor and normal tissues, and the correlation with PD-L1 expression. Conclusion: Overall, our results provide a deep insight into PMSC genes in LUAD, especially the prognostic effect and related immune profile which may predict therapeutic responses.